2015
DOI: 10.1136/vr.103187
|View full text |Cite
|
Sign up to set email alerts
|

Farming on the edge: farmer attitudes to bovine tuberculosis in newly endemic areas

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…The SPSS "Extract" command was used to extract variables describing these seven components for the regression analysis. Detailed descriptions of farmer perceptions and attitudes towards bTB are presented elsewhere (Enticott, Maye et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPSS "Extract" command was used to extract variables describing these seven components for the regression analysis. Detailed descriptions of farmer perceptions and attitudes towards bTB are presented elsewhere (Enticott, Maye et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The survey design and implementation has been described in detail by (Enticott, Maye et al 2015). The survey was thus designed to build on and extend work completed in previous epidemiological and social science research phases, combining social risk factors with farm practice and physical factors.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…This relatively weak influence of global prevalence, as opposed to local prevalence, has been also reported for farmers' trading behaviors. Although some farmers, but not all, avoid purchasing livestock from a high disease risk area for both endemic ( 32 , 33 ) and exotic diseases ( 34 , 35 ), it is unclear whether or not farmers are engaged in the risk-averse trading in response to disease prevalence. In fact, a UK study showed that the proportion of farmers from low bTB risk areas who mentioned they do not purchase cattle from high risk areas was larger than that of farmers from high bTB risk areas; however, farmers listed maintaining an existing trade channel as the main reason for this behavior ( 36 ).…”
Section: Disease-related Factors Relevant To Farmers' Dynamic Behaviomentioning
confidence: 99%
“…One of the most studied factors that contribute to forming farmers' descriptive belief may be actual disease experience. Enticott et al investigated practices and attitudes toward bTB among farmers in an area which had been recently designated as bTB endemic ( 32 ). This study found that the proportions of farmers that avoid purchasing from a high bTB risk area were similar between those previously had a bTB breakdown and those not ( 32 ), which may suggest a direct bTB experience may not necessarily change farmers' trading behaviors.…”
Section: Disease-related Factors Relevant To Farmers' Dynamic Behaviomentioning
confidence: 99%
“…Many of the stakeholders in this problem have polarised views and as such the problem has political dimensions that are similar to those around the debate about climatic change (Caplan, 2012;Nisbet & Markowitz, 2015). Stakeholders are broadly divided into those that feel that a wild animal reservoir host (in GB this would be badgers) is the principal cause of disease outbreaks by reintroducing infection to otherwise clean cattle herds, and those who feel that it is to cattle that attention needs to be directed and thus there is a conflict (King et al, 2007;Brooks-Pollock et al, 2014;Macdonald & Feber, 2015) -see also farmers view (Cowie et al, 2015;Enticott et al, 2015;O'Hagan et al, in press). The role of science in this debate should be to provide objective advice and guidance on the best way to tackle the disease.…”
Section: Introductionmentioning
confidence: 99%